Elucidation of serum interleukin-35 levels and interleukin-35 receptors in systemic lupus erythematosus patients: association with serological parameters and disease activity - Shukri, Nur Diyana Mohd (2021)
Background Interleukin-35 (IL-35) and IL-35 receptors are associated with the development of systemic lupus erythematosus (SLE). Many studies have been done recently to look into its association with autoimmune diseases, particularly SLE. This study aims to determine the serum IL-35 levels and the surface levels of IL-35 receptors (IL-12Rβ2 and gp130) on T helper cells in SLE patients versus healthy controls and their associations with serological parameters and disease activity. Method Fifty SLE patients were enrolled in the study and fifty volunteers were recruited as healthy controls. The percentage of CD3+CD4+ T helper cells and IL-35 receptors subunits IL-12Rβ2 and gp130 in peripheral blood mononuclear cells were analysed using flow cytometry. Serum IL-35 levels were measured by enzyme-linked immunosorbent assay (ELISA). SLE disease activity was evaluated using the Systemic Lupus Erythematosus Disease Activity Index-2K (SLEDAI-2K) score. Result The results showed that the mean serum IL-35 levels were significantly higher in SLE patients (31.53 ± 14.15 pg/ml) than those in the healthy controls (25.36 ± 7.073 pg/ml, p=0.038) whereas there was no significant difference among the mean IL-35 receptors (IL-12Rβ2 and gp130) levels in SLE patients compared to healthy control. In addition, IL-35 receptor subunit gp130 was positively correlated with the SLEDAI-2K scores (r=0.425, p=0.002). No significant association was observed between IL-35 and IL-35 receptor subunit IL-12Rβ2 and gp130 levels with the serological parameters in SLE patients. Conclusion Our findings demonstrated a significant increase in serum IL-35 levels in SLE patients and a positive correlation between IL-35 receptor subunit gp130 with SLEDAI-2K scores. Higher levels of gp130 on CD3+CD4+ T helper cells might play a role in the clinical manifestation of SLE, leading to more severe disease activity. Hence, they might serve as an essential biomarker and estimation for SLE disease activity and severity as well as for monitoring disease progression.